BERBAGAI MEDIA PEMBELAJARAN DI KELAS PADA PENDIDIKAN DASAR - Anggriani, Dewi (Journal of Education and Teaching, 2024)
There are many types of learning media that can be used by teachers in the teaching and learning process. Teachers must be able to choose the right type of learning media to be used in teaching and learning according to student learning needs. In essence, everyone has the right to get a good education so that later it will be useful for their life and future. Education is a field that focuses its activities on the teaching and learning process. There are various types of learning media that can be used to facilitate teachers in delivering subject matter to students.